Development of Plant-Based Kai Kolae Product - Nuankaew, Siriyakorn; Chalermchaiwat, Parisut; Sae-Tan, Sudathip (Journal of Food Technology, Siam University, 2025)
This research aimed to determine the optimal formula for a plant-based Kai Kolae product using a mixture design. The study investigated the effect of three main ingredients king oyster mushroom (Pleurotus eryngii) at 60–80%, jackfruit at 20–35%, and potato flour at 5–12% on the product's physical, chemical, and sensory properties. The results showed that varying the proportions of the three ingredients had no significant effect on the L*, a*, and b* color values of the product. Increased Pleurotus eryngii content led to higher adhesiveness and cohesiveness value including protein, crude fiber, and moisture content, but decreased hardness. Increasing of the jackfruit content resulted in lower springiness, while an increase in potato flour enhanced the chewiness and carbohydrate content but reduced fat. The formula with 70% Pleurotus eryngii, 21.5% jackfruit, and 8.5% potato flour received the highest overall sensory scores for all attributes, ranging from 6.18 to 6.90 points (Like slightly). The developed product consisting of 8.81% protein, 5.05% fat, 8.51% crude fiber, 3.53% ash, and 74.10% carbohydrates, providing an energy value of 4.38 kcal/g. Therefore, this product may be another healthy plant-based alternative for consumers.